Effect of Out of Pocket Cost on Following Mammography Screening - Shaiq Hussain, Pirya Nangdev, Bhagwan Das, Kailash Kumar Daseja, Sushma Qadir, Aneel Kumar (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To analyze the effect of out of pocket cost on subsequent mammography screening. Study design: Retrospective observational study Place and duration of study: Department of Radiology, Pir Abdul Qadir Shah Jeelani Institute of Medical Sciences, Gambat from 1st April 2021 to 31st March 2022. Methodology: One hundred female patients having ages 40-65 years with health insurances were followed from their baseline mammography screening up to their 12-36 months screening was enrolled. The clinical recorded, adjusted clinical group and other related information were documents. Results: 69% supported by a low deductible health policy while 31% were supported with a high deductible health policy The Adjusted Clinical Group score showed 74% within 0.3 scoring. For baseline mammography a decreased by 3.4% up to 12-24 months time was noticed. Conclusion: Out pocket cost has a significant effect of decreasing patient’s number for subsequent mammography screening. Keywords: Breast carcinoma, Mammography, Screening